A Fundamental-Analysis-Based Test for Speculative Prices - Curtis, Asher (The Accounting Review, 2012)
ABSTRACT I investigate the possibility that recent price movements include significantly larger speculative components than those observed historically, where speculation is defined as the component of price that does not co-move with fundamentals. Specifically, at the aggregate level, price and accounting fundamentals co-move historically (1979–1993) but do not co-move recently (1994–2008). The lack of co-movement in recent periods is accompanied by a significant reduction in the positive association between ratios of accounting fundamentals-to-price with future market returns. Changes in measurement error in accounting fundamentals do not appear to cause the lack of co-movement in recent periods, and risk- and growth-based explanations are not supported by the data. The results of this study provide evidence of a structural change in the long-run association between price and accounting fundamentals. Data Availability: Data are available from public sources identified in the study.